PROFILE OF AEDES BREEDING IN URBAN HIGH-RISE BUILDINGS: A CASE STUDY OF DENGUE OUTBREAK IN MALACCA, MALAYSIA - W. Yahya, Wan Nor Fareeda; Che Dom, Nazri (PLANNING MALAYSIA, 2020)
An understanding of dengue vector ecology plays an integral role in the effective elimination of vector breeding sites. The aim of this study was to assess the profile of the breeding habitat of the Aedes mosquito in urban high-rise buildings in Malacca. This study utilized epidemiological data from 2013 to 2017 to determine the distribution of dengue cases and Aedes breeding sites in high rise buildings. The Analytical Hierarchy Process (AHP) was used to evaluate the characteristics of Aedes breeding in high-rise buildings. In addition, the age and the total number of floors in the high-rise buildings were found to be important determinants of DF. The findings from this study will aid in the identification of target areas, which in turn can support future community-based search-and destroy intervention efforts. Furthermore, the conclusions of this research may guide the future design and construction features of high-rise buildings in Malaysia, which in turn can contribute toward a holistic and sustainable environment in the country.